The Bus Project: Technologies, Spectators and Locational Practices - Irwin, Kathleen (Theatre Research in Canada / Recherches théâtrales au Canada, 2008)
This paper interrogates the claim made by many users of super-technologies in the field of theatre entertainment that these trappings redefine audience perception in entirely new ways. What this explosion fails to address is the relationship between technology and the spectating body and how interactivity poses questions that address the specificities of the spectator in the twenty-first century. In relative magnitude, The Bus Project described here, was low tech. Nonetheless, it illustrates the use of interactive technologies in integrating performance into our everyday lives, how new audiences may be reached and how preconceived notions of spectatorship and identity may be productively troubled through locational and site-specific practices. The Bus Project was a collaborative, media-based, public art installation undertaken by theatre and intermedia artists, computer scientists and graduate students at the University of Regina in June 2004. The central focus of the project was to open up the idea of multiculturalism and the anxieties that have grown up around the multiple coding of this term by investigating issues of immigration in the local communities (Regina and Saskatoon). As the project moved from planning to implementation, the nature of interdisciplinarity, community collaboration and assessment became central to the investigation. Résumé Bien des utilisateurs de super technologies au théâtre déclarent que ces « ornements » font en sorte que les spectateurs perçoivent les choses tout à fait autrement. Or, l’explosion de ces moyens ne dit rien du rapport qu’entretient le public avec eux et n’interroge pas l’effet de l’interactif sur la spécificité du spectateur au XXIe siècle. En termes d’importance, The Bus Project, le spectacle qui sert d’exemple ici, employait des moyens relativement rudimentaires. Et pourtant, il montre comment l’on peut user de technologies interactives pour intégrer la performance à la vie quotidienne, atteindre de nouveaux spectateurs et remettre en question de façon productive nos idées préconçues sur le spectateur et l’identité au moyen de pratiques localisées. The Bus Project est une installation média à laquelle ont participé des artistes de théâtre et des artistes multimédia, des informaticiens et des étudiants de deuxième cycle à l’Université de Regina en juin 2004. Le projet avait pour principal objectif de présenter l’idée du multiculturalisme et les anxiétés qui entourent la codification complexe du terme en examinant les enjeux liés à l’immigration dans les villes de la région (Regina et Saskatoon). Au cours de sa réalisation, l’enquête s’est centrée peu à peu sur l’interdisciplinarité du projet et la participation des membres de la collectivité, devenus collaborateurs et évaluateurs.